Broader perspectives on motion event descriptions - Matsumoto, Yo, 1960-; Kawachi, Kazuhiro (Human cognitive processing ;, 2020)
"Human languages exhibit fascinating commonalities and variations in the ways they describe motion events. In this volume, the contributors present their research results concerning motion event descriptions in the languages that they investigate. The volume features new proposals based on a broad range of data involving different kinds of motion events previously understudied, such as caused motion (e.g., kick a ball across) and even visual motion (e.g., look into a hole). Special attention is also paid to deixis, a hitherto neglected aspect of motion event descriptions. A wide range of languages is examined, including those spoken in Europe, Africa, and Asia. The results provide new insights into the patterns languages deploy to represent motion events. This volume will appeal to anyone interested in language universals and typology, as well as the relationship between language and thought"--